Thyroglossal cyst at unusual site: a rare case presentation - Janardan, Toshi; Bhatia, Jas Simran Singh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Thyroglossal duct cyst is a congenital lesion in the anterior side of neck which results from embryonic remnant of the descending thyroglossal duct. It may get enlarge by infection, inflammation or mucous retention but can be found anywhere in the midline from the base of the tongue to thyroid gland. Most commonly it is present infrahyoid only. In this case, it is present at an unusual site at suprasternal region. A young male presented in the OPD with a single, non-tender swelling in the midline at suprasternal region, almost reaching upto superior mediastinum. After radiological examination and histopathological excision biopsy, it came out to be thyroglossal cyst. No recurrence had occurred.